2022
DOI: 10.1029/2022gl097726
|View full text |Cite
|
Sign up to set email alerts
|

Global Increases in Compound Flood‐Hot Extreme Hazards Under Climate Warming

Abstract: Under global warming, a novel category of extreme events has become increasingly apparent, where flood and hot extremes occur in rapid succession, causing significant damages to infrastructure and ecosystems. However, these bivariate compound flood‐hot extreme (CFH) hazards have not been comprehensively examined at the global scale, and their evolution under climate warming remains unstudied. Here, we present the first global picture of projected changes in CFH hazards by using a cascade modeling chain of CMIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…An HW_HI/HW_TW event occurring prior to an HP event, within a given time window, is defined as an HWHP event (noted as HWHP_HI and HWHP_TW, respectively) (Lombardo and Ayyub, 2015;Zhang and Villarini, 2020;Chen et al, 2021;Liao et al, 2021;Wu et al, 2021;You and Wang, 2021;Gu et al, 2022;Ning et al, 2022). The window is chosen as 3 days in this study, which is the same as previous studies (Lombardo and Ayyub, 2015;Zhang and Villarini, 2020;Chen et al, 2021;Liao et al, 2021;Wu et al, 2021;You and Wang, 2021;Gu et al, 2022;Ning et al, 2022). In the following analyses, we also examine whether our results are sensitive to the choice of the time window (e.g., 2, 4, and, 7 days).…”
Section: Identification Of Sequential Heatwave-heavy Precipitation Ev...mentioning
confidence: 99%
See 4 more Smart Citations
“…An HW_HI/HW_TW event occurring prior to an HP event, within a given time window, is defined as an HWHP event (noted as HWHP_HI and HWHP_TW, respectively) (Lombardo and Ayyub, 2015;Zhang and Villarini, 2020;Chen et al, 2021;Liao et al, 2021;Wu et al, 2021;You and Wang, 2021;Gu et al, 2022;Ning et al, 2022). The window is chosen as 3 days in this study, which is the same as previous studies (Lombardo and Ayyub, 2015;Zhang and Villarini, 2020;Chen et al, 2021;Liao et al, 2021;Wu et al, 2021;You and Wang, 2021;Gu et al, 2022;Ning et al, 2022). In the following analyses, we also examine whether our results are sensitive to the choice of the time window (e.g., 2, 4, and, 7 days).…”
Section: Identification Of Sequential Heatwave-heavy Precipitation Ev...mentioning
confidence: 99%
“…Chen et al (2021) found the increased sequential flood-heatwave events across China and indicated that increased HW events dominate the increased compound events. Gu et al (2022) projected increases in bivariate compound flood-heatwave hazards globally under future warming and attributed these increases to enhancing HW events.…”
Section: Spatial Clustering and Changes In The Extent Of Hwhp Eventsmentioning
confidence: 99%
See 3 more Smart Citations